Economic sanctions in American foreign policy - BENHAMZA, Fayza (Journal of Human Sciences, 2020)
The economic sanctions mechanism research in the US foreign policy makes us stand on one fact that can not be ignored that the essence of this policy is to achieve the supreme national interest of the country at the expense of all considerations and values with the use of force in all its forms including economic sanctions to dominate the world out of the international legitimacy within a range of styles and methods through which America tried to give a kind of legitimacy on its decisions and actions thus America with its foreign policy constitutes a kind of tyranny.